Sanqi Panax Notoginseng Injection for Angina Pectoris. (16th February 2014) - Yang, Xiaochen; Xiong, Xingjiang; Wang, Jie
Abstract : Objective . To evaluate the clinical curative effects of SPN injection on AP. Methods . Six databases were systematically searched including Cochrane Central, PubMed, EMBASE, CBM, Chinese National Knowledge Infrastructure (CNKI), and VIP to identify randomized controlled trials (RCTs). We assessed the quality of included studies, extracted valid data, and undertook meta-analysis following the steps of systematic review recommended by the Cochrane group. Results . Ten moderate-to-low quality randomized controlled trials involving 969 patients were included. There was no evidence that SPN alone had better or worse effects than conventional drugs on improving clinical symptoms (RR 1.09, 95% CI 0.85 to 1.39) and ECG (RR 1.17, 95% CI 0.84 to 1.63). However, there was an evidence that SPN combined with western medications was a better treatment option than conventional drugs alone in improving clinical symptoms (RR 1.28, 95% CI 1.19 to 1.33) and ECG (RR 1.27, 95% CI 1.12 to 1.45). No serious adverse effects were reported. Conclusion . Compared with conventional treatment, SPN may show the potential of optimizing symptomatic outcomes. As a kind of alternative and complementary medicine, SPN may provide another choice for AP patients and further large-scale high-quality trials are needed to confirm this efficacy.